BILIARY FISTULAS ASSOCIATED WITH LIVER TRANSPLANTATION VERSUS OTHER ETIOLOGIES: WHAT IS THE SUCCESS RATE OF THE ENDOSCOPIC TREATMENT? - MARINHO,Leonardo (2022)
ABSTRACT - BACKGROUND: Biliary fistulas typically occur as surgical complications after laparoscopic cholecystectomy, liver transplantation, or partial liver resection. AIMS: This study aimed to evaluate the efficacy of the endoscopic treatment of biliary fistulae secondary to liver transplantation compared to that of other etiologies. METHODS: A retrospective study of 25 patients undergoing endoscopic retrograde cholangiopancreatography for biliary fistula from 2015 to 2021 was conducted at the Endoscospy Unit of Walter Cantídio University Hospital. Clinical characteristics and endoscopic success rates of the post-liver transplantation group were analyzed in comparison with those of other etiologies. RESULTS: The main causes of biliary fistula were liver transplantation (44%) and cholecystectomy complications (44%). The post-liver transplantation group had a significantly higher proportion of male sex (liver transplantation=81.8%, others=28.6%) and older age (liver transplantation=54.1 years, others=42.0 years) and a higher incidence of biliary stenosis (liver transplantation=90.9%, others=14.3%) than those of the group with other etiologies (p<0.05). The two groups received similar treatment types, among which sphincterotomy associated with biliary stent placement was most commonly used. Endoscopic therapeutic success rates showed no significant difference between the post-liver transplantation group (63.6%) and the group with other etiologies (71.4%). CONCLUSIONS: The endoscopic treatment of biliary fistulae secondary to liver transplantation presented a recovery rate similar to that of other etiologies despite the patients older age and the presence of biliary stenosis